Optimized Tapping Frequency and Ethrel Dosage for Latex Production: Frekuensi Pemanenan dan Dosis Ethrel yang Dioptimalkan untuk Produksi Lateks - Akhmad Sopian; Afrilianus Ferdinan; Siti Mutmainah (Universitas Muhammadiyah Sidoarjo, 2025)
General Background: Rubber productivity in Indonesia remains low due to suboptimal cultivation practices, including the improper use of stimulants, which can harm plant health. Specific Background: One strategy to increase yield is the application of low tapping frequency combined with Ethrel 10 PA stimulant, which can prolong latex flow and enhance cell metabolism; however, its effectiveness depends on clone type and plant physiological condition. Knowledge Gap: Limited knowledge exists on the optimal combination of tapping frequency and stimulant dosage to sustain productivity without compromising plant health, particularly for PB 260 and GT 1 clones. Aims: To determine the optimal tapping frequency and stimulant dosage for these clones. Results: Field trials revealed that a d/3 tapping frequency yielded the highest latex output, while a dosage of 2 g/tree produced the maximum yield; however, there was no significant interaction between the two factors. High tapping frequency, though productive, risks reducing plant health. Novelty: This study recommends tapping every four days combined with a 1 g/tree Ethrel dosage to balance productivity and plant health. Implications: These findings provide practical guidance for sustainable rubber cultivation, maximizing yield while preserving the productive lifespan of trees. Highlights: Optimal combination of tapping interval and stimulant dosage. Balances high yield with plant health preservation. Practical recommendation for sustainable rubber farming. Keywords: Rubber Productivity, Tapping Frequency, Ethrel 10 PA, Latex Yield, Sustainable Cultivation